Dos conselhos de classe aos conselhos participativos de classe: o papel na escola pública e a relação com as políticas educacionais que se afirmam democráticas - Lourenço, Zely Fernanda (2019)
This study presents the results of the research carried out with the purpose of studying the Participatory Class Councils, based on their historical contextualization, in order to discuss their relationship with the educational policies that are claimed to be democratic and their subsequent role in the public school and in the implementation of democracy in school. The research aims to verify if the Participatory Class Councils in the current public school exercise a democratic function as suggested by the laws and policies that regulate them. In order to do so, we chose the framework of critical theory to treat and analyze the object of study. The research was carried out in two state public schools in the municipality of São José dos Campos / SP, which attend students from the 1st to 3rd year of secondary school in the night, in which data were collected to obtain information through documentary analysis of the Minutes of the Class Participatory Councils, legislation, and educational policies that govern Class Participatory Councils. The analysis of the documents allowed to conclude that the Participative Councils of Class based on the speeches of democratic opening, by itself, do not guarantee practices or democratic performances, because they are subverted by the institutionalization and bureaucratization that place limits on the possibilities of participation effectively democratic